2007
DOI: 10.1002/chem.200601151
|View full text |Cite
|
Sign up to set email alerts
|

Electrocyclic Ring Opening of cis‐Bicyclo[m.n.0]alkenes: The Anti‐Woodward–Hoffmann Quest

Abstract: The dubbed anti-Woodward-Hoffmann ring-opening reaction of cis-bicyclo[4.2.0]oct-7-ene to yield cis,cis-cycloocta-1,3-diene has been intensively studied with robust, high-level computational methods. This reaction has been found to proceed through a conrotatory allowed pathway to afford cis,trans-cycloocta-1,3-diene followed by E to Z isomerization, instead of a disrotatory forbidden pathway, as suggested. Computational calculations of kinetic isotope effects are consistent with this interpretation and the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Collectively, the spectroscopic data indicated that trans -poly­(acetylene) was obtained as the only detectable product from the methodology described above, which was a surprising result and prompted us to postulate potential mechanisms (see Scheme ). Although previous reports have shown that certain cyclobutenes and related polyladderenes can undergo selective electrocyclic ring-opening, mixtures of cis and trans products may result when the precursors feature assorted stereoisomers. , Because the spectroscopic data recorded for 9 indicated that the material was composed of a single stereoisomer, an alternative route wherein ring-opening proceeds through a radical intermediate that isomerizes to the thermodynamically favored ( trans ) polymer product was considered.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Collectively, the spectroscopic data indicated that trans -poly­(acetylene) was obtained as the only detectable product from the methodology described above, which was a surprising result and prompted us to postulate potential mechanisms (see Scheme ). Although previous reports have shown that certain cyclobutenes and related polyladderenes can undergo selective electrocyclic ring-opening, mixtures of cis and trans products may result when the precursors feature assorted stereoisomers. , Because the spectroscopic data recorded for 9 indicated that the material was composed of a single stereoisomer, an alternative route wherein ring-opening proceeds through a radical intermediate that isomerizes to the thermodynamically favored ( trans ) polymer product was considered.…”
Section: Results and Discussionmentioning
confidence: 99%
“…2629 No such transition structure was found using spin-restricted B3LYP; however, use of broken symmetry, spin-unrestricted B3LYP successfully yielded structure 8a (Figure 5). This result clearly indicates diradical character, which is known to exist in transition structures of π-bond rotation.…”
Section: Resultsmentioning
confidence: 99%
“…As a guess geometry, we used the TS geometry computed in ref. 178. This guess geometry has C s symmetry, and we note that the reactant and product have a common (i.e.…”
Section: A Woodward-hoffmann Violating Reactionmentioning
confidence: 94%
“…8). Theoretical ground-state studies 177,178 have shown that the added carbon atom, which starts off in a cyclopropyl group, serves to force the molecule into a ring-opening disrotatory motion that entails a TS.…”
Section: A Woodward-hoffmann Violating Reactionmentioning
confidence: 99%